(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2025)
The integration of artificial intelligence (AI) into public administration has rapidly expanded, with particular potential in optimizing judicial processes. While global judicial systems—from the U.S. and EU to China and Singapore—have pursued varying models of AI deployment, Uzbekistan is actively formulating its own approach amid ongoing digital reforms. Despite a growing global discourse on AI in justice, a comprehensive framework tailored to Uzbekistan’s legal, institutional, and technological context remains underdeveloped. This study analyzes international AI applications in judiciary systems and evaluates Uzbekistan’s strategic steps toward legal and institutional adaptation. Uzbekistan’s advancements include the launch of the “E-Sud” portal, approval of a national AI strategy, and development of regulatory mechanisms such as the draft Law “On the Regulation of Relations in the Field of AI.” These initiatives are reinforced by ethical standards focusing on transparency, human oversight, and rights protection. The article provides a comparative and contextualized analysis of AI adoption in judicial systems, proposing an original framework that aligns international best practices with Uzbekistan’s legal environment. The findings underscore the importance of gradual implementation, institutional readiness, and ethical safeguards. The study concludes that human discretion must remain central, and that AI should serve as a supportive tool—enhancing, but not replacing, judicial decision-making in Uzbekistan’s evolving digital justice model.